Structure of the motor subunit of type I restriction-modification complex EcoR124I - Lapkouski, Mikalai; Panjikar, Santosh; Janscak, Pavel; Smatanova, Ivana Kuta; Carey, Jannette; Ettrich, Rüdiger; Csefalvay, Eva (Nature structural & molecular biology, 2009)
Type I restriction-modification enzymes act as conventional adenine methylases on hemimethylated DNAs, but unmethylated recognition targets induce them to translocate thousands of base pairs before cleaving distant sites nonspecifically. The first crystal structure of a type I motor subunit responsible for translocation and cleavage suggests how the pentameric translocating complex is assembled and provides a structural framework for translocation of duplex DNA by RecA-like ATPase motors.
Keywords: Protein Subunits; Deoxyribonucleases, Type I Site-Specific; Protein Conformation; podjednotky proteinů; Models, Molecular; molekulární modely; restrikční endonukleasy typu I; Binding Sites; adenosintrifosfát; Adenosine Triphosphate; vazebná místa; konformace proteinů